MAXIMUM TORQUE PER AMPERE (MTPA) STRATEGY ON A 120 KW BLDC MOTOR FOR MEDIUM ELECTRIC BUS APPLICATION - Mushthofa Musyasy, Muhammad
The application of electric motors has spread in various lives of modern society today, one of which is transportation. One type of motor that is often used is the Brushless DC (BLDC) motor. To drive a BLDC motor, a controller is needed so that the motor has good performance when operating. This final project research aims to create and analyze the Maximum Torque Per Ampere (MTPA) control strategy algorithm, which is a control strategy that aims to minimize motor phase current at a torque output, and the appropriate control system for a 120 kW BLDC motor, both as torque and speed control. The Mercedes-Benz OF-917 bus was chosen as a benchmark to make it easier to determine load parameters. The results of this study are the MTPA strategy requires a smaller phase current than the Modified Field Oriented Control (MFOC) method with a magnitude of 0.14% to 1.27% with a performance that is not much different. The regenerative braking algorithm has been simulated with the results of having the same performance as the MFOC method and when the source is reduced, the motor performance is not reduced too significantly. This MTPA control strategy is better used for larger or equal to 250 Nm of output torque because the torque ripples and currents are smaller than the MFOC method.